2021
DOI: 10.1007/978-981-33-4183-8_50
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Trends of the Absorption Refrigeration Global Market

Abstract: This study presents the evolution and economic development of the global market for absorption refrigeration systems. The article reviews trends in demand for high and lowpower absorption refrigeration systems. High growth potential was found in low-power absorption refrigeration systems in the global market. An important finding is that the most widely installed systems in the world are those of single effect and double effect, due to their cost/benefit ratio. It also reviews the relations and trends of compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Further research has demonstrated the feasibility of solar-powered absorption cooling systems in shopping malls by means of different working fluids to improve the heat transfer and COP with computational sources, experiments, and tests in commercial facilities (Alhamid et al, 2020;Amaris, 2013;Rodríguez-Toscano et al, 2022a;Zapata et al, 2021). However, there is scarce information available on absorption refrigeration systems installed on the market that involves biomass as another energy source for their activation, along with the use of solar energy (Ayou et al, 2013;Ghafoor & Munir, 2015; A. D. R. Toscano et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Further research has demonstrated the feasibility of solar-powered absorption cooling systems in shopping malls by means of different working fluids to improve the heat transfer and COP with computational sources, experiments, and tests in commercial facilities (Alhamid et al, 2020;Amaris, 2013;Rodríguez-Toscano et al, 2022a;Zapata et al, 2021). However, there is scarce information available on absorption refrigeration systems installed on the market that involves biomass as another energy source for their activation, along with the use of solar energy (Ayou et al, 2013;Ghafoor & Munir, 2015; A. D. R. Toscano et al, 2021).…”
Section: Introductionmentioning
confidence: 99%